2020
DOI: 10.1001/jamapediatrics.2019.5669
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of C-Reactive Protein Diagnostic Test Accuracy for Late-Onset Infection in Newborn Infants

Abstract: IMPORTANCE Rapid and accurate diagnosis of late-onset infection in newborn infants could inform treatment decisions and avoid unnecessary administration of antibiotics.OBJECTIVE To compare the accuracy of serum C-reactive protein (CRP) with that of microbiological blood culture for diagnosing late-onset infection in newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 54 publications
1
57
0
Order By: Relevance
“…CRP is the most commonly available test in hospitals for neonatal sepsis [ 10 , 11 , 21 , 22 ]. It is both used for diagnosing sepsis and monitoring disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CRP is the most commonly available test in hospitals for neonatal sepsis [ 10 , 11 , 21 , 22 ]. It is both used for diagnosing sepsis and monitoring disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is both used for diagnosing sepsis and monitoring disease progression. However, a recent meta-analyses by Brown and colleagues in 2255 infants showed that CRP is insensitive and nonspecific for LONS diagnosis [ 11 ]. Based on the kinetics of CRP, it is not preferred as an early prognostic and diagnostic marker; however, it has been shown that serial measurements of CRP could reliably rule-out infection 24 h after suspicion [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be more useful in excluding infections in suspected cases and enable earlier discontinuation of antibiotics. This may be cost-effective, decreasing the development of resistance and hospital stay duration [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRP can interact with DNA and histones, and it may scavenge nuclear material released from damaged circulating cells. The concentration of CRP in plasma increases greatly during acute phase response to tissue injuries, infections, cancers, and renal and cardiovascular diseases [ 2 ]. It is induced by interleukin-1 and interleukin-6.…”
Section: Introductionmentioning
confidence: 99%